Community perceptions of the implementation and impact of an intervention to improve the neighbourhood physical environment to promote walking for transport: a qualitative study - Emma J. Adams; Lauren B. Sherar (BMC, 2018)
Abstract Background Using community engagement approaches to develop and deliver interventions targeting small-scale physical environmental improvements in neighbourhoods is a potential strategy for increasing walking for transport. This study aimed to qualitatively assess community perceptions of the implementation and impact of the Fitter for Walking (FFW) intervention, which encouraged communities to work together to improve the street environment on local routes and promote walking for transport. Methods From 155 FFW community projects, nineteen were selected to take part in a focus group/interview using specified criteria: geographical area; level of community involvement; intervention activities; and project progress. Participants were invited to take part via the project coordinator or lead member of the community group. A written guide was used to initiate and direct discussions through key topics. Deductive and inductive approaches were used to analyse the data and identify key themes relating to the barriers and facilitators for implementation and the perceived impact of the intervention. Results Fourteen focus groups and five interviews were conducted with 86 community members. Themes were identified in relation to barriers (poor area reputation and regeneration areas; engaging the local community; and working with local authorities) and facilitators (provision of a coordinator/facilitator; strong local partnerships; and using a range of communication and engagement activities) for programme implementation. Participants perceived the main impacts to be improved physical and social environments. Increases in walking for transport were rarely specifically commented on, but participants did report increased street use. Conclusions Community perspectives provided important insights into the barriers and facilitators for the implementation of the FFW intervention and its' potential impacts. Using community engagement approaches can lead to perceived improvements in the physical and social environment resulting in increased street use, which may lead to increases in walking for transport in the longer-term. Recommendations are provided for researchers, practitioners and policy makers in planning and delivering future interventions. Future research should determine optimal implementation strategies, investigate the relative importance of improving physical environments, social environments and using individual behaviour change strategies, and determine how physical and social environments interact to maximise intervention impact on walking for transport.